1999
DOI: 10.1053/euhj.1998.1203
|View full text |Cite
|
Sign up to set email alerts
|

Increased binding of fibrinogen to glycoprotein IIIa-Proline33 (HPA-1b, PlA2, Zwb) positive platelets in patients with cardiovascular disease

Abstract: The increased tendency of platelets from patients with the Pro33 form of GPIIIa may predispose patients with this allele to a higher risk of acute thrombotic events, and argues for selective use of therapeutic agents that inhibit ADP-mediated platelet activation in occlusive vascular disease states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 31 publications
4
56
1
3
Order By: Relevance
“…39 In addition, Goodall and coworkers found increased fibrinogen binding to Pl A2 platelets stimulated by ADP, but not when the platelets were stimulated by thrombin. 59 On the other hand, Meiklejohn and colleagues reported that there was no difference in fibrinogen binding to ADP-stimulated Pl A1 and Pl A2 platelets. 60 We found that the presence of a single Pl A2 allele had no effect when fibrinogen binding was measured as a function of ADP concentration.…”
Section: Discussionmentioning
confidence: 98%
“…39 In addition, Goodall and coworkers found increased fibrinogen binding to Pl A2 platelets stimulated by ADP, but not when the platelets were stimulated by thrombin. 59 On the other hand, Meiklejohn and colleagues reported that there was no difference in fibrinogen binding to ADP-stimulated Pl A1 and Pl A2 platelets. 60 We found that the presence of a single Pl A2 allele had no effect when fibrinogen binding was measured as a function of ADP concentration.…”
Section: Discussionmentioning
confidence: 98%
“…We found that one variant of these polymorphisms, the Pl A2 allele, was associated with heightened platelet aggregability as indicated by a lower epinephrine threshold concentration. 11 Although these findings were supported by studies with thrombin receptoractivating peptide (TRAP) 12,13 and ADP, 27 the association between the Pl A2 and increased platelet aggregability has not been consistent. For example, Lasne et al 28 found that platelets of Pl A2 -positive genotype needed higher concentrations of TRAP to induce platelet dense granule secretion.…”
Section: Gp Iiia Polymorphism Fibrinogen and Platelet Aggregabilitymentioning
confidence: 99%
“…The difference is not caused by altered platelet receptor density. 27,30 One possible explanation is that the mild platelet aggregability change produced by the genetic variation could be masked when a large fixed concentration of agonist is used. 29 In addition, studies with small sample sizes may not have the power to detect differences.…”
Section: Gp Iiia Polymorphism Fibrinogen and Platelet Aggregabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Данные о влиянии СОТ на содержание ГП IIb-IIIa соответствуют результатам, недавно опубликованной работы [16], выполненной в сходных группах доноров и пациентов. Отсутствие каких-либо эффектов ГП IIIa Leu33Pro полиморфизма на уровень экспрессии ГП IIb-IIIa подтверждают как наши собственные данные, полученные ранее при исследовании здоровых добровольцев [14], так и данные других авторов [12,13,29,30]. В обеих исследованных нами группах -здоровых добровольцев и больных с ОКС была впервые обнаружена сильная взаимосвязь между СОТ и содержанием еще одного адгезивного рецептора тромбоцитов -ГП Ib.…”
Section: рисунокunclassified